PENGARUH TINGKAT PENDIDIKAN DAN KESEMPATAN KERJA TERHADAP PENGANGGURAN DI PROVINSI BANTEN - Samsul Arifin; Firmansyah Firmansyah (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Unemployment in the province of Banten became a huge unemployment in Indonesia, with the figure reaching 10.74 percent. This is particularly worrying given the province of Banten Province is newly established and is known for a large industrial sector that should be able to absorb the unemployment rate and the labor force. And the study was conducted to examine the effect of higher education graduates and the chance to unemployment in the province of Banten. The analytical method used is regression analysis with panel data in the form of secondary data for a period of nine years from 2003 to 2011. Test analysis used partial statistical test (t-test) with a 95 percent degree of confidence, measured by the F test and R2 test (test determinants). Results of this study have used the hypothesis that if the number of higher education graduates up it will lower the number of unemployment rose when the number of jobs it will reduce the number of unemployed. The conclusion that can be drawn in this paper is that the increase in the number of graduates of higher education will affect the unemployment rate falling.. Employment do not affect the decline in the unemployment rate.